Career assistant/deputy principals : asleep at the wheel or motivated drivers in education? : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Education, Institute of Education, Massey University - Shore, Kevin (Massey University, 2015)
This study focuses on a largely unrecognised group of secondary school assistant/deputy principals who have no desire to pursue principalship. Findings from the study have shown that these assistant/deputy principals who, for the purpose of this study are called ‘career AP/DPs’, play a significant role in the leadership of New Zealand secondary schools yet there is little research focused on the assistant/deputy principalship as a vocation. Consequently, the intentions of this study are to develop a more complete understanding of this group in order to ensure that career AP/DPs are a recognised group of educational leaders with a distinct mission to support principals in leading our New Zealand secondary schools. The research design employed a mixed methods approach. It used a survey questionnaire to identify those AP/DPs who identify as career AP/DPs and then focus group interviews with selected groups of career AP/DPs to develop a more complete understanding of the group. The findings from the study highlight that career AP/DPs have followed a serendipitous career journey where key colleagues have been crucial in championing their leadership aspirations. Career AP/DPs gain satisfaction from the daily contact that they have with students, caregivers and staff and enjoy the psychological rewards that come from making a difference in their schools. However, they are clearly disappointed that they are not able to make a wider contribution to teaching and learning in their schools and advocate for a more significant role in this portfolio. Career AP/DPs are strongly attached to their leadership teams including the principal and acknowledge them as the most significant professional support they have providing the conditions for them to grow and fully enjoy the psychological rewards that come from serving in this position.
Keywords: Shore, Kevin